Screening for antibiotics in endophytes isolated from melastoma malabathricum from Lundu, Sarawak - Munirah, Abdul Talip (Universiti Malaysia Sarawak (UNIMAS), 2010)
A study was conducted to isolate and screen endophytes from Melastoma malabathricum for antibiotic activity. Ten samples from three plants were collected from Lundu, Sarawak, and used for the isolation. Of the ten fungal endophytes that were isolated, four fungal isolates, namely E1, E2, E3 and E4, were considered separate isolates. In a preliminary antimicrobial activity test using agar overlay technique, only isolates E2 and E3 showed zone of inhibition against test bacteria. In this test, E2 was positive against both Gram positive bacteria, Staphylococcus aureus and Gram negative bacteria, Escherichia coli. E3 showed positive result against Gram negative bacteria, E. coli. Further antimicrobial activity test on E2 and E3 using agar overlay technique, revealed a contrasting results in which E2 was only positive against S. aureus and that E3 was positive against E. coli. However, antifungal activity screening showed that all four fungi isolates did not against the test fungus, which was Fusarium sp. Antibiotic screening test was also carried out on methanol extracts of the four endophytes. In agar disc diffusion test, methanol extract of E2 gave positive result against both S. aureus and Salmonella typhii. Methanol extract of E1 also gave positive result against S. aureus and S. typhii, but the inhibition zone produced were not clearly shown. Methanol extracts of E3 and E4 were not active against the test bacteria. Macroscopic and microscopic observations using slide culture technique showed that the four endophytic fungi had different characteristics. The colonies of E1 and E4 were white, whereas E2 was purplish-brown, and E3 was grey in colour. All three isolates E1, E2, and E3 possessed dark, septate, and brancing hyphae while E4 was hyaline, septate and non-branching hyphae. The spores of E1 and E2 were both cylindrical in shape, while E3 and E4 did not sporulate. The isolates E1 and E2 were tentatively identified as Fusarium sp. and Chalaropsis sp respectively. The E3 and E4 fungal isolates were non-identified.